PEMBERIAN ROOTONE F TERHADAP PERTUMBUHAN STEK BATANG PURI (Mitragyna speciosa Korth) - Cahyadi, Okta; AM, Iskandar; Ardian, Hafiz (Universitas Tanjungpura, 2017)
Puri (Mitragyna speciosa Korth) is one of the plant that has a high economic value, especially in Kapuas Hulu which has been used extensively by the community by taking the leaf of the plant that grows naturally in the forest. This research aims to determine the dose of Rootone F on the growth of stem cuttings of puri. This research was conducted for 2 month. The method used was Completely Random Design, which consisted of 4 treatments with 8 repetitions. Each treatment wash given with concentration Rootone F of 0 ppm, 50 ppm, 100 ppm and 150 ppm. The variables measured were percentage of growing, number of shoots and number of roots. The results showed that adding Rootone F on stem cuttings of puri at 100 ppm had a significant effect on the growth parameter of the number of shoots and a very significant effect on the parameter of the number of roots. The growth percentage of the stem cuttings of puri was 72%. Â Keywords: Interaction, Mitragyna speciosa Korh, Rootone F